Vacuum-Assisted Wound Therapy in Bothrops Snakebite Injuries: A Case Series from the Brazilian Amazon - Carbonell, Roberto C. C. [UNESP]; Garcês-Filho, Allan Q.; Galan, Luis E. B.; Romanazzi, Marcela [UNESP]; Malachias-Pires, Geovanna M. [UNESP]; Almeida, José R.; Nattrodt, Jânio J. M.; de L. B. Carbonell, Joquebede; Cerni, Felipe A.; Vaiyapuri, Sakthivel; Pucca, Manuela B. [UNESP] (MDPI, 2025)
In Brazil, snakebites are a critical health issue, particularly in the state of Roraima, where Bothrops species account for the majority of cases. Snake venoms contain multifunctional toxins that cause life-threatening systemic complications and complex wounds, often resulting in permanent disabilities. Although antivenoms have reduced lethality, they fail to prevent the rapid and prolonged action of tissue-damaging toxins at the bite site. As a result, snakebite management is characterized by prolonged hospitalizations and high healthcare costs. Therefore, effective management of these complex wounds is crucial to improving patient outcomes. This article presents a series of four clinical cases involving Bothrops snakebite patients treated at the General Hospital of Roraima. Each case describes the progression of the injury, clinical challenges, interventions, and outcomes. Vacuum-Assisted Wound Therapy (VAWT) was employed as a key component of treatment in all cases, promoting faster granulation tissue formation, infection control, and reduced risk of amputation. The use of VAWT demonstrated significant improvements in wound healing compared to conventional treatment approaches. These findings highlight the potential benefits of VAWT in managing complex snakebite-related wounds, especially in severe cases with high risks of complications. However, barriers such as the high cost of therapy and limited access in remote and resource-poor regions must be addressed to enable broader clinical application.